MAKNA SUBTANTIF DAN ESTETIS PADA MAKAM RAJA-RAJA DI PANTAI TIMUR KALIMANTAN - Bambang Sakti Wiku Atmojo (Balai Arkeologi Kalimantan Selatan, 2008)
In the east coast of Kalimantan, which stretches from north to south from districts of Bulungan, Berau, Kutai Kertanegara, Paser, Kotabaru, and Tanah Bumbu, archaeological remains of the Islamic periode are abundantly founds comprising palaces and the old burials. Evidences of the old sultanate grandeur are commemorated on a number of places. For instance, based on the result of 2000-2004 research, there were 21 burial compounds of the sultans burials discovered with rich carving on their grave markers and jirat. The carving indicate 6 varieties of design i.e. geometric, floral, arabesque, Arabic calligraphy, Latin scrip and lontarak. This article will discuss about the fundamental and aesthetic significance of ornamentation on the sultan’s burials on the east coast of Kalimantan.